Establishing a Pathway to Excellence® Research Agenda: A Delphi Study to Identify Research Priorities for Evaluating Positive Practice Environments. (14th March 2023) - Mulvey, Tanya; Cámpoli, Marcela; Lundmark, Vicki
Abstract : OBJECTIVE: The aim of this study was to develop research priorities for positive practice environments identified by Pathway to Excellence® (Pathway) leaders and appraisers. BACKGROUND: Identifying research priorities achieves 2 goals: 1) advancing research agendas that impact improving practice environments, and nurse and patient outcomes; and 2) informing nursing leaders, researchers, and funders of potential research projects to conduct and support. METHODS: Research topics related to the 6 Pathway standards were developed and then rated for importance through 3 rounds of a Delphi survey by leaders at Pathway-designated organizations and Pathway appraisers. RESULTS: Twenty research priorities were identified from the initial 54 research topics. The top 2 priorities were building and maintaining shared governance participation (91.9%) and nurse participation in performance improvement and evidence-based practice activities (90.7%). CONCLUSIONS: Establishing a Pathway research agenda will guide nursing leadership, researchers, and funders in selecting impactful research priorities to help bolster positive practice environments that engage and empower nurses.